Synodality, the Synod Structure and Ecclesia Semper Reformanda - Abeyasingha, Nihal (Asian Horizons, 2020)
The Catholic Church is constituted of 24 Individual Churches—23 from the Eastern tradition and the Roman Church (Western). They are in communion of faith and fellowship. In the East there is a synodal structure of governance. Pope Paul VI constituted the Synod of Bishops (1965), not as an instrument of governance, but as an instrument of the widest possible consultation in the whole church. It consists of Bishops and other officials of the Western Church plus Bishops and representatives of the Eastern Churches. Fifty years later, Pope Francis has introduced the possibility of the Synod of bishops sharing in the ordinary papal magisterium. However, both the synodal structure of the East and the synod of bishops are institutions that take on the forms of this passing world and therefore in need of constant reform (cf. LG 48). The tension is between synodality (an ideal) and synodal governance/ synodal consultation (an institutional, therefore, imperfect, form of the ideal). This tension will never be resolved permanently. There is and will be the embodiment/ institution versus the call of the spirit inviting to constant discernment and conversion.